The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/1467-6427.12021
|View full text |Cite
|
Sign up to set email alerts
|

Thematic review of Family Therapy Journals 2012

Abstract: In this article the contents of the principal English‐language family therapy journals, and key family therapy articles published in other journals in 2012 are reviewed under these headings: therapy processes in the treatment of child‐focused problems, autism, adolescent substance use, human immunodeficiency virus, depression and grief, fragile families, mental health recovery, medical family therapy, family business and systemic practice, couple therapy, intimate partner violence, key issues in theory and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…BD has two distinct pathological phases, a depressed phase similar to an MDD episode and an mania or hypomanic phase presenting with periods of elated mood and increased energy. A systematic review of 44 articles looking at different subtypes of ELS (sexual abuse, physical abuse, emotional abuse, physical neglect, and emotional neglect) concluded that mood disorders are associated with all forms except emotional neglect (151).…”
Section: Mood Disordersmentioning
confidence: 99%
“…BD has two distinct pathological phases, a depressed phase similar to an MDD episode and an mania or hypomanic phase presenting with periods of elated mood and increased energy. A systematic review of 44 articles looking at different subtypes of ELS (sexual abuse, physical abuse, emotional abuse, physical neglect, and emotional neglect) concluded that mood disorders are associated with all forms except emotional neglect (151).…”
Section: Mood Disordersmentioning
confidence: 99%
“…Attributions play a role in defining the intentions of the person exhibiting the problem behavior. When family members attribute negative characteristics or intentions to each other, these attributions may lead them to persist in problem-maintaining behavior and elicit problem-maintaining behavior in others (Carr, 2013). Belief systems also support and maintain problem behaviors through attribution of intent to other behaviors and beliefs about the relationship.…”
Section: Principle #3: Problem Narratives and Attributions Form The M...mentioning
confidence: 99%